Sistem Penunjang Keputusan Untuk Evaluasi Kinerja Guru Menggunakan Metode Simple Additive Weghting (Studi Kasus : SMA N 1 Katibung) - Desky Triyasbudi Nugraha; Dodi Afriansyah; Akhmad Ikhwan (Universitas Mitra Indonesia, 2022)
Every last semester, Katibung 1 Senior High School always got the evaluation about teacher performance that scored by the headmaster or builder of the teacher that chosen by the headmaster, partner of the teacher, and the students that input a questionnaire. Data processing was scored from questionnaire, has been computerized with using a google forms. However no especially apps yet that is processing data . where the is resulting information is not effective and efficient , because needing the time for processing data of the result questionnaire and in the process of the teacher performance determination error may occurred.